2020
DOI: 10.1111/ggi.14021
|View full text |Cite
|
Sign up to set email alerts
|

Serum growth differentiation factor 15 level is associated with muscle strength and lower extremity function in older patients with cardiometabolic disease

Abstract: Aims: Sarcopenia is a serious problem because of its poor prognosis. Growth differentiation factor 15 (GDF15) is associated with mitochondrial dysfunction, inflammation, insulin resistance and oxidative stress, which may play crucial roles for the development of sarcopenia. We aimed to examine whether serum GDF15 level is associated with muscle mass, strength and lower extremity function in older patients with cardiometabolic disease. Methods: Serum GDF15 levels were measured in 257 patients with cardiometabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 34 publications
1
29
1
Order By: Relevance
“…Our results are consistent with several studies that have found associations between elevated serum GDF-15 levels and a sarcopenic phenotype [7][8][9][10][11][12][13]. However, there are some notable inconsistencies in the associations between serum GDF-15 levels and ASM in human studies: there are reports of a significant association between GDF-15 levels with ASM before and after adjustment for confounders [8,11], no association, [12], and non-significant associations after adjustment for confounders [9,10,12,13]. Although we could not explain inconsistencies in the associations reported in previous studies [8][9][10][11][12][13], age-related increases in plasma GDF-15 (γ = 0.556) might be responsible for the inconsistencies.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are consistent with several studies that have found associations between elevated serum GDF-15 levels and a sarcopenic phenotype [7][8][9][10][11][12][13]. However, there are some notable inconsistencies in the associations between serum GDF-15 levels and ASM in human studies: there are reports of a significant association between GDF-15 levels with ASM before and after adjustment for confounders [8,11], no association, [12], and non-significant associations after adjustment for confounders [9,10,12,13]. Although we could not explain inconsistencies in the associations reported in previous studies [8][9][10][11][12][13], age-related increases in plasma GDF-15 (γ = 0.556) might be responsible for the inconsistencies.…”
Section: Discussionsupporting
confidence: 93%
“…However, there are some notable inconsistencies in the associations between serum GDF-15 levels and ASM in human studies: there are reports of a significant association between GDF-15 levels with ASM before and after adjustment for confounders [8,11], no association, [12], and non-significant associations after adjustment for confounders [9,10,12,13]. Although we could not explain inconsistencies in the associations reported in previous studies [8][9][10][11][12][13], age-related increases in plasma GDF-15 (γ = 0.556) might be responsible for the inconsistencies. The present study shows significant associations between GDF-15 levels and BMI-adjusted ASM and sarcopenia, not only in the unadjusted model, but also in the adjusted model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inverse correlation between muscle mass and circulating GDF-15 levels is not speci c to CD and has been reported in patients with chronic obstructive pulmonary disease [22], pulmonary arterial hypertension [23], and preoperative cardiovascular disease [24]. Moreover, an inverse association between GDF-15 and MS or function has also been reported in patients with cardiometabolic disease [25] and cancer [26], and in healthy community-dwelling adults [27]. Although the exact mechanisms of serum GDF-15 elevation in CD patients with low SMI remain unknown, some evidence suggests that GDF-15 may promote muscle wasting.…”
Section: Discussionmentioning
confidence: 92%
“…Low body mass index (BMI) is a risk factor for exaggerated decline in the lung function, and is an independent predictor of the overall mortality in COPD (64), and is a bad prognostic indicator in the BODE index; which is used to predict the mortality risk among COPD patients (65). Elevated levels of GDF15 are associated with low muscle mass and strength, in aging patients (66,67). In COPD patients, it was associated with a sedentary lifestyle and cognitive risk (68).…”
Section: Role Of Gdf15 In Chronic Obstructive Pulmonary Disease (Copd)mentioning
confidence: 99%